Electrochemical impedance spectroscopy characterization of passive film formed on implant Ti-6Al-7Nb alloy in Hank's solution - Lavos-Valereto, I. C.; Wolynec, S.; Ramires, I; Guastaldi, Antonio Carlos [UNESP]; Costa, I (Springer, 2004)
The influence of potential on electrochemical behavior of Ti-6Al-7Nb alloy under simulate physiological conditions was investigated by electrochemical impedance spectroscopy (EIS). The experimental results were compared with those obtained by potentiodynamic polarization curves. All measurements were carried out in Hank's aerated solution at 25degreesC, at pH 7.8 and at different potentials (corrosion potential, 0 mV(SCE), 1000 mV(SCE), and 2000 mV(SCE)). The EIS spectra exhibited a two-step or a two-time constant system, suggesting the formation of a two-layer oxide film on the metal surface. The high corrosion resistance, displayed by this alloy in electrochemical polarization tests, is due to the dense inner layer, while its osseointegration ability can be ascribed to the presence of the outer porous layer. (C) 2004 Kluwer Academic Publishers.